Analysis of Special Assistance Teachers' Needs for Hypermedia-Integrated Science Learning Modules in Junior High School - Riska, Elena; Kustandi, Cecep; Winarsih, Murni (CV. Media Digital Publikasi Indonesia, 2024)
This study aims to analyse the needs of special assistant teachers in the subject of Natural Science (IPA) at the School of Human Junior High School. The method used was a qualitative approach. Data collection was carried out through observation of 4 special assistant teachers who were conducting the learning process. After that, researchers conducted in-depth interviews with 8 special assistant teachers. The results of this study indicate that special assistant teachers need a guidebook as a guide for them in dealing with children with special needs in science subjects. This is because special assistance teachers experience difficulties when the class becomes unconducive. In addition, the material related to biological science is a challenge for special assistant teachers in training children with disabilities to memorise the material. So, the hypermedia integrated science learning module is an alternative guide for special assistance teachers. They not only read the guide but can also listen and observe the steps in the science learning process through the hypermedia integrated learning module. This study concluded that with the existence of science learning modules, special assistance teachers can improve their pedagogical competence. Therefore, this research has implications for inclusive education through the development of hypermedia-integrated learning modules that can provide convenience for special assistant teachers in dealing with the obstacles of the learning process for children with disabilities in the classroom